Menara Teratai Purwokerto: Potensi Urban Tourism sebagai Sumber Pendapatan Baru bagi Kota - Naeli Zakiyah Agustina; Annisa Khusnaeni; Baros Galang Jiwa; Laylli Nur Wakhidah; Yoiz Shofwa Safrani (JURNAL ILMIAH NUSANTARA, 2025)
Urban tourism is a form of tourism based on urban life and dynamics, which is now a global trend in the development of modern tourist destinations. This research is to analyze and identify the potential of Menara Teratai Purwokerto as an urban tourism object and its contribution to the increase of Regional Original Revenue (PAD). This study employs a qualitative descriptive approach through observation and literature study approach. The analysis shows that the Lotus Tower is not only a visual icon and a new public space in Purwokerto City, but also holds educational values such as ethnomathematical elements and philosophical symbols that reflect social harmonization and local culture. The development of the area around the tower also encourages community economic mobility, expands the tourist zone, and opens up new opportunities for the creative economy sector. With proper and participation-based governance, Menara Teratai possesses the capability to become a sustainable source of revenue for the city.